Conditions for improving basic sports training of 13-14-year-old boxers - Nazarenko, L. D.; Kolesnik, I. S. (Journal of Physical Education and Sport, 2017)
At the basic stage of learning, sports training of 13-14-year-old boxers should maintain the interest in a chosen type of sports activity with regard to motivation. This predetermines the necessity of searching for new approaches to the sports training of boxers, finding external and latent properties, abilities, and capacities of the organism to achieve future goals in sports. This research investigates the conditions for improving basic sports training of adolescents. Such conditions determine the training efficiency and competitive activities, raise the number of successful bouts, and requires considering demands for the purpose of sportsmanship improvement. This ensures not only the maintenance, but also sparks the interest in boxing, which evolves into a need for training load and self-fulfillment by means of the chosen sport.